A Textbook based on Community-based Learning: Its Validity, Practicality and Effectiveness - Hesti Wahyuni Anggraini; Zuraida; Tita Ratna Wulan Dari; Juliantina (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Persistent difficulties in academic writing among EFL learners reflect a deeper structural problem, namely the disconnection between decontextualized instructional materials and students’ lived experiences. Addressing this gap, this study introduces a Community-Based Learning (CBL) textbook that reconceptualizes writing instruction as a process of transforming real-world engagement into structured academic discourse. Using a design-based research approach, the study was conducted through iterative phases of analysis, design, evaluation, and revision involving 23 undergraduate students and two lecturers in an Indonesian higher education context. Data were collected through questionnaires, interviews, observations, and writing tests, and analyzed using descriptive statistics and thematic analysis. The findings reveal that students’ writing difficulties are multidimensional, encompassing linguistic limitations, constrained idea generation, and weak paragraph organization, all of which are intensified by the absence of contextual learning opportunities. The developed textbook demonstrated high validity, strong usability, and substantial instructional effectiveness, evidenced by expert validation results and improved student writing performance during field testing. Crucially, the integration of community-based tasks enabled students to generate meaningful content, strengthen coherence, and construct more logically organized paragraphs. This study extends existing theories of experiential and sociocultural learning by operationalizing them into a coherent instructional material design, rather than treating them as isolated pedagogical strategies. By positioning textbook design as a central mediator of experiential, cognitive, and social learning processes, this research provides a novel and scalable framework for contextualized writing instruction, offering a significant contribution to the global advancement of EFL writing pedagogy